Determination of carboxyhaemoglobin and methaemoglobin levels in donated blood (Research, Society and Development, 2021)
To determine the percentages of carboxyhaemoglobin (COHb) and methaemoglobin (MeHb) in donor blood and to compare these levels between smokers and nonsmokers at different time points during blood storage. Blood donors were recruited from Haematology Service, University Hospital Alzira Velano, Alfenas-MG. The blood was kept in collecting ducts (noodles) containing citrate, phosphate and dextrose (CPD) and stored at 4°C throughout the storage period. Since the noodles kept the characteristics of the bags, COHb and MeHb levels were analysed on the day of donation and after 20 days of storage. Levels of COHb and MeHb were determined using spectrophotometric methods. Non-parametric Friedman and Mann-Whitney tests were employed to compare COHb and MeHb levels before and after the storage and groups of smokers and nonsmokers, respectively. Levels of COHb and MeHb in the blood collected from smokers and nonsmokers were statistically different (p< 0.05; Mann- Whitney test) when the samples were analyzed before the storage. In blood of smokers, COHb levels were no different over a 20-day storage period (p= 0.7009; Friedman test). On the other hand, MeHb levels were significant different over a 20-day storage period (p< 0.05). The results suggest the need to regularly assess COHb and MeHb levels in donor blood stored in blood banks.